Structures and key concepts in the current aesthetic phenomena: Taste, cool and new base aesthetics - Aragó Miñana, María del Mar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Starting from aesthetics as a discipline of knowledge, this research revolves around different concepts, phenomena and trends that participate in aesthetics. Decoding elements such as taste, cool and new aesthetics, or analyzing phenomena such as bad taste, we delimit a broad and abstract conception of aesthetics. Exposing these aspects allows us to promote a general point of view that makes aesthetic meta-information accessible, revealing its mechanisms, dynamics and intrinsic structures. Due to its influence on the configuration of the context, the conforma-tion of subjectivity and the production of collective imaginaries and, therefore, of society, we understand aesthetics as a discipline that allows the knowability of its environment, conditioning other spheres such as the political, the economic or the anthropological.